Predicting feedlot performance using mathematical models - P. George; B.E. Brent (Kansas Agricultural Experiment Station Research Reports, 1979)
Tables based on mathematical models illustrate how feed intake, rate of gain, and feed efficiency change during the feeding period and in response to different wing-chill temperatures. The tables wert used to calculate costs or gain.
Keywords: Cattlemen' s Day; 1979; Report of progress (Kansas State University. Agricultural Experiment Station); 350; Beef; Feedlot performance; Feed intake; Rate of gain; Feed efficiency